Profesor Lorenzo Mérola. Maestro de Cirugía 1880-1935 - de Chiara, Juan Carlos; Valls, Alberto; Sarroca, Carlos; Balboa, Oscar (Cirugía del Uruguay, 1981)
100 years ago, on February 29, I was born inMontevideo Lorenzo Mérola, who was latera distinguished Master of Surgery. 100 years ago, on February 29, Lorenzo Mérola was born in Montevideo, which was latera distinguished Master of Surgery.Tribute made at the Uruguayan Society of Surgery on July 23, 1980, commemorating the centenary of his birth.It includes:The aponeurosis of the armpit / Lorenzo MérolaModified radical mastectomy. Mérola Operation / Alberto Valls, Carlos SarrocaMérola thoracic-abdominal approachChest - abdominal approach (commentary) / Oscar BalboaGastroplasty with colon / Lorenzo MerolaTranstentorial occipital approach to the pineal gland / Pedro Benedek